2022-VA-633-ESGO Standardized LEER procedure. (20th October 2022) - Lago, Víctor; Segarra-Vidal, Blanca; Padilla-Iserte, Pablo; Matute, Luis; Gurrea, Marta; Pérez Álvarez, Jose Antonio; Domingo, Santiago
Abstract : Introduction/Background: Recurrence of cervical cancer is a challenge especially in patients who have received Radiochemotherapy for local extension at diagnosis. It is relatively common to find, in case of recurrence, situations where the hypogastric vessels, obturator muscle and nerve are affected. Methodology: The procedure called lateral extended endopelvic resection (LEER) was described by Hoekel et al. for surgical resection of lateral pelvic recurrences. We present a video surgery describing the vascular and nervous anatomy of the lateral pelvis and a case of 4-D reconstruction of the tumour and surgical resection of the tumour. Results: LEER + Radical Hysterectomy + ureteral reimplantation + intraoperative radiotherapy was performed in a patient referred to our department for a single recurrence of cervical cancer on the right side of the pelvis after primary treatment with RT-QT. Complete resection of the tumour was achieved as shown in the video with un eventful post operative period. Free of disease after 2 years. Conclusion: With thorough anatomical knowledge, surgical resection of the lateral pelvic compartment is possible in case of recurrences.